Evaluation of sheep grazing as a tool to restore mountain pastures invaded by Euphorbia polygalifolia - Mora M.J.; Busqué J.; Hervás G.; Mantecón A.R.; Fernández B.; Frutos P. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Two experiments were conducted to (i) study whether sheep grazing pastures infested by a spurge (Euphorbia polygalifolia) consume this invasive weed and its consequences on animal performance, and (ii) detect differences between sheep and cattle in ruminal degradation of infested pastures. In the first trial, sheep grazed fenced paddocks highly invaded by spurge at instantaneous stocking rates of 120 ewes/ha/week. Spurge offtake, sward height and ewes' body weight were measured weekly from mid-June to September. An average of 63% of the initial spurge growing points was defoliated per week. Sward height showed a negative curvilinear relationship with the proportion of spurge defoliated, with high spurge defoliation occurring when sward height was lower than 4 cm. Variation in body weight was mainly related to sward height (r = 0.86; P<0.10) and apparent signs of intoxication were never observed. In the second experiment, 6 cows and 8 ewes were distributed according to a factorial design: 2 species (cattle vs sheep) × 2 grazing areas (infested vs non-infested pastures). After seventeen days, rumen fluids were used to study ruminal fermentation of invaded and noninvaded pastures using the in vitro gas production technique. Gas production was always higher in sheep than in cows when the invaded substrate was incubated (P<0.05). The highest values were found in sheep grazing infested pastures and the lowest in cattle maintained in non-infested pastures. This suggests not only a better ruminal degradation of E. polygalifolia by sheep but also a likely adaptation to its consumption.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)